A Nomogram Model to Predict Prognosis of Patients With Genitourinary Sarcoma - Li, Linde; Liang, Jiayu; Song, Turun; Yin, Saifu; Zeng, Jun; Zhong, Qiang; Feng, Xiaobing; Jia, Zihao; Fan, Yu; Wang, Xianding; Lin, Tao (Frontiers in Oncology, 2021)
Abstract: Objectives: The aim of this study is to evaluate the significant factors influencing the overall survival (OS) and recurrence free survival (RFS) and make an attempt to develop a nomogram for predicting the prognosis of patients with genitourinary sarcoma (GS). Methods: Data on adult GS from 1985 to 2010 were collected. The impact of clinical factors on OS and RFS were estimated by Kaplan-Meier (KM) analysis, and differences between groups were analyzed by the log-rank test. To establish a nomogram, all patients were randomly divided into a training set and a testing set . Then, a nomogram was established to estimate OS based on Cox regression model. Subsequently, the nomogram was validated by training set and validation set. Results: A total of 188 patients were enrolled into our study. Male patients with bladder sarcoma had better OS rather than RFS when stratified by gender (P=0.022). Patients with leiomyosarcoma (LMS) undergoing chemotherapy were associated with favorable OS (P=0.024) and RFS (P=0.001). Furthermore, LMS in kidney sarcoma were associated with lower recurrence rate in comparison to rhabdomyosarcoma (RMS) (P=0.043). Margin status after surgical excision markedly influenced the OS and RFS of GS patients and negative margins presented optimal prognosis. Chemotherapy was associated with improved OS for patients without surgery (P=0.029) and patients with positive margins (P=0.026). Based on the multivariates analysis of training cohort, age, gender, surgery status, histological subtype and chemotherapy were included in our nomogram for prediction of OS. The nomogram had sufficient power with concordance index (C-index) of OS: 0.770, 95%CI:0.760-0.772 and area under curve (AUC) of OS: 0.759, 95%CI:0.658-0.859 in the training set and with C-index of OS :0.741, 95%CI:0.740-0.765 and AUC of OS:0.744, 95%CI:0.576-0.913 in the validation set. Conclusions: Adults GS is a group of extremely rare tumors with poor prognosis. LMS is sensitive to chemotherapy. We highlighted the cardinal role of surgical resection and the importance of achieving negative margins. We identified the efficacy of chemotherapy for some patients. A nomogram is validated as an effective tool predicting short-term outcomes.